IMPLEMENTATION OF FINANCIAL MANAGEMENT OF THE AL-HIDAYAH TAKLIM COUNCIL IN IMPROVING THE ECONOMY OF MEMBERS - Uzlan Uzlan; Siti Maryam (IJED: International Journal of Economy Development Research, 2023)
Financial management is the management of financial functions that involve the use of funds. This is important for the long-term success of an organization as it helps manage funds efficiently.  This research uses liquidity management theory and Islamic financial liquidity management theory as a basis for analyzing financial management at Majelis Taklim Al-Hidayah. The purpose of this research is to find out 1.) How does the financial management system of Majlis Ta'lim Al-Hidayah improve the members' economy? 2.) How does the implementation of financial management of Majelis Taklim Al-Hidayah contribute to improving the member's economy. This research uses a qualitative method with a case study approach. Data was obtained through in-depth interviews with majlis administrators and members, as well as direct observation of the majelis' financial activities. In addition, an analysis of the majelis financial documents was carried out to gain a comprehensive understanding of the financial management implemented. The results of this research show that 1.) That the financial management system at Majelis Taklim Al-Hidayah involves regular and systematic cash management, including budget creation and neat cash flow recording. This cash management ensures that funds are always available for daily operational needs and religious activities. 2.) Majelis Taklim Al-Hidayah has implemented various programs to improve the economy of its members. The interest-free loan program helps members address urgent financial needs, such as education and health, without burdening them. Simple application requirements and flexible returns according to member capabilities. The business capital assistance program supports members in starting or growing their businesses by providing interest-free loans to those who have a clear business plan.